From Satire to Naturalism – Ante Babaja’s Short Film - Putyńska, Urszula (Poznańskie Studia Slawistyczne, 2024)
This article aims to analyze and interpret Ante Babaja’s short films (both fiction and documentary). These works can be seen as a kind of laboratory of themes and means of expression representative of the Croatian director’s work. The reconstruction undertaken reveals the evolution of Babaja’s artistic path, which can be simply described as a shift from a satirical to a naturalistic form of representation. Both tendencies are synthesized in later feature-length productions, along with a number of artistic devices specific to Babaja’s work.